Astaxanthin, meclizine, mitoglitazone, pioglitazone, alpha-ketoglutarate, mifepristone, methotrexate, and atorvastatin-telmisartan do not increase lifespan in UM-HET3 mice - Ron Korstanje; Randy Strong; Adam B. Salmon; Molly A. Bogue; Sean P. Curran; Vivian Diaz; Elizabeth Fernandez; Brett Ginsburg; Melissa Han; David E. Harrison; Catherine Kaczorowski; Matt Kaeberlein; et al. (GeroScience, 2026)

Extension of lifespan by epicatechin, halofuginone and mitoglitazone in male but not female genetically heterogeneous mice - Randy Strong; James F. Nelson; Molly A. Bogue; Jerry R. Colca; Martin Denzel; Vivian Diaz; Brian N. Finck; Vadim N. Gladyshev; Steve Horvath; Nisi Jiang; Tracy Keller; Rolf F. Kletzien; et al. (GeroScience, 2025)
Mice bred in 2021 were tested by the Interventions Testing Program (ITP) for possible lifespan benefits of 2BAct (2BA), dichloroacetate (DCA), Epicatechin (EPI), Forskolin (FSK), Halofuginone (HAL) and Mitoglitazone (MIT). All agents were administered in the diet ad libitum beginning at 7 months of age. In male mice, EPI increased median lifespan by ~ 5%, and HAL and MIT each increased median lifespan by ~ 9%. EPI and HAL, but not MIT, increased 90% survival. In addition to adding 3 new agents to the list of interventions identified by the ITP that extend lifespan, this report continues the strong male bias in the efficacy of life-extending drugs identified so far.

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16-hydroxyestradiol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2025)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16‑hydroxyestriol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Nisi Jiang; Catherine C. Kaczorowski; Navasuja Kumar; et al. (GeroScience, 2024)

Lifespan effects in male UM-HET3 mice treated with sodium thiosulfate, 16-hydroxyestriol, and late-start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2024)

Astaxanthin and meclizine extend lifespan in UM-HET3 male mice; fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate do not significantly affect lifespan in either sex at the doses and schedules used - David E. Harrison; Randy Strong; Peter Reifsnyder; Nadia Rosenthal; Ron Korstanje; Elizabeth Fernandez; Kevin Flurkey; Brett C. Ginsburg; Meredith D. Murrell; Martin A. Javors; Marisa Lopez-Cruzan; James F. Nelson; et al. (GeroScience, 2023)
In genetically heterogeneous (UM-HET3) mice produced by the CByB6F1 × C3D2F1 cross, the Nrf2 activator astaxanthin (Asta) extended the median male lifespan by 12% ( p = 0.003, log-rank test), while meclizine (Mec), an mTORC1 inhibitor, extended the male lifespan by 8% ( p = 0.03). Asta was fed at 1840 ± 520 (9) ppm and Mec at 544 ± 48 (9) ppm, stated as mean ± SE ( n ) of independent diet preparations. Both were started at 12 months of age. The 90th percentile lifespan for both treatments was extended in absolute value by 6% in males, but neither was significant by the Wang–Allison test. Five other new agents were also tested as follows: fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate. None of these increased lifespan significantly at the dose and method of administration tested in either sex. Amounts of dimethyl fumarate in the diet averaged 35% of the target dose, which may explain the absence of lifespan effects. Body weight was not significantly affected in males by any of the test agents. Late life weights were lower in females fed Asta and Mec, but lifespan was not significantly affected in these females. The male-specific lifespan benefits from Asta and Mec may provide insights into sex-specific aspects of aging.

Canagliflozin retards age-related lesions in heart, kidney, liver, and adrenal gland in genetically heterogenous male mice - Jessica M. Snyder; Kerriann M. Casey; Andrzej Galecki; David E. Harrison; Hashan Jayarathne; Navasuja Kumar; Francesca Macchiarini; Nadia Rosenthal; Marianna Sadagurski; Adam B. Salmon; Randy Strong; Richard A. Miller; et al. (GeroScience, 2023)
Canagliflozin (Cana), a clinically important anti-diabetes drug, leads to a 14% increase in median lifespan and a 9% increase in the 90th percentile age when given to genetically heterogeneous male mice from 7 months of age, but does not increase lifespan in female mice. A histopathological study was conducted on 22-month-old mice to see if Cana retarded diverse forms of age-dependent pathology. This agent was found to diminish incidence or severity, in male mice only, of cardiomyopathy, glomerulonephropathy, arteriosclerosis, hepatic microvesicular cytoplasmic vacuolation (lipidosis), and adrenal cortical neoplasms. Protection against atrophy of the exocrine pancreas was seen in both males and females. Thus, the extension of lifespan in Cana-treated male mice, which is likely to reflect host- or tumor-mediated delay in lethal neoplasms, is accompanied by parallel retardation of lesions, in multiple tissues, that seldom if ever lead to death in these mice. Canagliflozin thus can be considered a drug that acts to slow the aging process and should be evaluated for potential protective effects against many other late-life conditions.